2021
DOI: 10.29312/remexca.v12i8.2704
|View full text |Cite
|
Sign up to set email alerts
|

Agricultura intensiva y calidad de suelos: retos para el desarrollo sustentable en Sinaloa

Abstract: En una dimensión regional, se analizan dos factores claves de la actividad agrícola de Guasave, Sinaloa, México que influyen directamente en el desarrollo rural sustentable: la agricultura intensiva y la calidad de suelos. La presente investigación se diseñó como un estudio cualitativo de tipo descriptivo de este ramo productivo, para ello se aplicaron 164 entrevistas a productores y se analizaron diversos documentos con información del sector, tales como informes técnicos y boletines. Se encontró que la agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Regarding the promotion of monocultures, 27.20% of the respondents expressed that they were undecided on this statement. In Sinaloa, intensive agriculture is centred on maize production, which directly and indirectly impacts the sustainable development of the sector [16]. A total of 32.80% recognised that the government did not promote monocultures, while 40% indicated that it did (see Figure 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the promotion of monocultures, 27.20% of the respondents expressed that they were undecided on this statement. In Sinaloa, intensive agriculture is centred on maize production, which directly and indirectly impacts the sustainable development of the sector [16]. A total of 32.80% recognised that the government did not promote monocultures, while 40% indicated that it did (see Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…With reference to [16], the most frequent agricultural practices in Guasave are gravity irrigation, soil movements such as tracking, cultivation and fallowing, and the use of synthetic inputs and agrochemicals. These practices have negative impacts that can lead to problems such as poor soil quality, poor water conditions, risk to groundwater, and in some cases, a decrease in production, which would indicate unsustainable agricultural patterns [17].…”
Section: Introductionmentioning
confidence: 99%
“…Es así que los circuitos cortos y largos de consumidores se articulan con el propósito de proporcionar los elementos estructurales necesarios que posibiliten el fortalecimiento de los sistemas productivos agrícolas, en específico el de maíz, con el propósito de atender los aspectos relacionados con la seguridad y soberanía alimentaria (Cuadras-Berrelleza et al, 2021).…”
Section: Resultsunclassified
“…Such agricultural production systems provide elements for resilience to the environmental, health and food crises that affect us today. In addition, considering the conservation of natural resources such as soil and water during agricultural production and access to food for the population (Cuadras-Berrelleza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%